DESIGN OF A RELIGIOUS LOCAL CONTENT CURRICULUM BASED ON RELIGIOUS CULTURE IN SCHOOLS - Lamuhtadun; Rofiatul Hosna (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2021)
This study aims to analyze the design of a religious local content curriculum based on religious school culture and its implications for students’ spiritual character formation. The research employed a qualitative case study approach conducted in an elementary school. Data were collected through in-depth interviews, observations of learning and religious habituation activities, and documentation of curriculum plans and school programs. Data analysis was carried out through data reduction, display, and verification using triangulation techniques to ensure credibility. The findings reveal that the curriculum design is grounded in the school’s religious vision and translated into learning outcomes focusing on practical worship skills, Qur’anic literacy, memorization of prayers, and habituation of Islamic moral conduct. The implementation is integrated with structured religious habituation programs such as congregational dhuha prayer and routine Qur’anic recitation. Evaluation emphasizes practical assessment and daily behavioral monitoring. The curriculum effectively fosters a religious school culture reflected in disciplined worship, proper conduct, and students’ spiritual awareness.